Respon Pertumbuhan dan Hasil Tomat (Lycopersicum esculentum Mill.) terhadap Pemberian Dosis Pupuk NPK Mutiara dan Teknik Pemangkasan Cabang - Diana Diana; Kahar Kahar; Fandi Ahmad (Program Studi Agroteknologi, Fakultas Pertanian Universitas Madako Tolitoli, 2025)
This study aimed to evaluate the effect of the interaction between NPK Mutiara fertiliser dosage and branch pruning on the growth and yield of tomato plants (Lycopersicum esculentum Mill.). The experiment was carried out from March to May 2024 at the experimental field of the Faculty of Agriculture, Madako University, Tolitoli, Tambun Village, Baolan District, Tolitoli Regency. A factorial Randomised Block Design (RBD) was used with two factors: NPK Mutiara fertiliser dosage (0 g/plant, 15 g/plant, and 25 g/plant) and branch pruning (no pruning, leaving three main branches, and leaving four main branches). Each treatment combination was replicated three times, resulting in 27 experimental units. The results revealed a significant interaction between NPK Mutiara fertiliser and branch pruning on plant height (51.92 cm) and fruit weight per sample (391.50 g). The single factor of branch pruning had a highly significant effect on fruit diameter at 67 days after planting (48.47 mm) and 74 days after planting (57.86 mm), with the best performance observed in treatments leaving 3–4 main branches. Overall, applying NPK Mutiara fertiliser at 25 g/plant combined with pruning to 3–4 main branches enhanced the growth and yield of tomato plants.